المقاصد القرآنية في القصص القرآني- قصة آدم عليه السلام أنموذجا- - جاب الله, سمية (University of Eloued جامعة الوادي, 2017)
تناول هذا البحث المقاصد القرآنية في القصص القرآني من خلال قصة آدم عليه السلام دراسة موضوعية وذلك باستقراء آيات القصة وبيان مقاصدها. فبينت أولا تعريف المقاصد وبيان أهميتها وبيان المفسرين لهذه المقاصد ثم تعريف القصة في القرآن الكريم وبيان المقاصد القرآنية في القصص القرآني، وبيان منهج وخصائص القصة في القرآن، ثم قمت بدراسة مقاصد قصة آدم عليه السلام وذلك ببيان مقصد كل موضع من قصة آدم وذكرت آيات كل موضع وبيان المعنى العام للآيات وأهم المقاصد القرآنية لها، وبعدها ذكرت مقصد التكرار من القصة، وبينت أنه لا تكرار في القصة فهو من باب التنوع . وفي الأخير توصلت في هذا البحث إلى نتائج منها من مقاصد قصة آدم عليه السلام بيان وحدة الوحي الإلهي والتحذير من غواية العدو المبين. This research deals with the Quranic purposes in the Quranic stories through the story of Adam, peace be upon him, an objective study by reading the verses of the story and explaining its purposes. At the beginning I mentioned the definition of the purposes and the statement of its significance and the interpretation of the interpreters for these purposes and then the definition of the story in the Koran and the purposes of the Koran in the Quranic stories. I also mentioned characteristics of the story in the Koran and it’s methodology , then I studied the purposes of the story of Adam peace be upon him And the general meaning of the verses and the most important purposes of the Koran, and then mentioned the purpose of repetition of the story, and indicated that any repetition in the story is part of diversity. Finally, in this research, I found out of the results that the story of Adam (peace be upon him), show the unity of the divine revelation and the warning against the eternal enemy.
مذكرة ماستر تخصص تفسير علوم القرآن
Keywords: القصص القرآني- المقاصد القرآنية- قصة آدم- التكرار.; Quranic stories- Quranic Purposes- the story of Adam- rebetition